Discovering the South : One Man's Travels through a Changing America in the 1930s - Ritterhouse, Jennifer Lynn (Book collections on Project MUSE., 2017)
"In the summer of 1937, Jonathan Daniels, the young, white, liberal-minded editor of the Raleigh News and Observer, took a ten-state driving tour to 'discover' his native land. He thought the true South lay somewhere between Erskine Caldwell's Tobacco Road and Margaret Mitchell's Gone with the Wind, and he set out to find it--ultimately interviewing even Mitchell herself. In this book, historian Jennifer Ritterhouse pieces together Daniels's unpublished notes from his tour along with his published writings and a wealth of archival evidence to put this ... observer's journey through a South in transition into a larger context"--